Non-tariff measures and the WTO - Robert W. Staiger (World Trade Organization (WTO), 2012)
In this paper I sketch out the rough contours of the challenge faced by the WTO in dealing with non-tariff measures (NTMs) as seen from the economic theories of trade agreements. The key questions for the WTO - the answers to which largely dictate the choice between shallow and deep approaches to integration - appear to be two: (1) Is it the terms-of-trade problem or the commitment problem that WTO member governments seek to solve with their WTO membership?; and (2) Is it market clearing or offshoring/bilateral bargaining that is now the most prominent mechanism for the determination of international prices? I suggest that evidence on the first question points to the terms-of-trade theory and hence toward shallow integration, but that answering the second question may be the key to identifying the best way forward on NTMs for the WTO.
Keywords: D62; F13; F55; H21; H23; 330; terms of trade; commitment; border measures; behind-the-border measures; offshoring; bilateral bargaining; Nichttarifäre Handelshemmnisse; WTO-Regeln; Terms of Trade; Außenwirtschaftstheorie